Manage IT!: foundation of records management / Siti Noorsiah Jamaludin, Siti Nuur-Ila Mat Kamal and Alwi Mohd Yunus - Jamaludin, Siti Noorsiah; Mat Kamal, Siti Nuur-Ila; Mohd Yunus, Alwi (UiTM Press, 2019)
Information is the life-blood of an organisation that should be managed effectively, so that the information is available to the right person, at the right time, and the right place which must be protected from unauthorised access. However, records management was not recognised as being important in an organisation. Therefore, this book has been successfully made to promote the existence of records management professional in Malaysia and the important of records management in organisation. Manage It! Foundation of Records Management book is intended to be a reference book for students mainly in Information Management and Records Management, Faculty of Information Management. This book is also essential to be used as a reference for records custodians and others who have any responsibility for records management programmes. This book is formulated as a guideline on how to manage records effectively and systematically in organisation. This book is divided into several sections based on a particular point in aspect of records management. The chapters provide an overview of terms and basic concept of records management, principles of records management, records management legislation, registry as a place to manage your records, file management, and appraisal and disposition of records in organisation, accordingly. It also consists of diagrams and tables. At the end of the chapters, the summary is worded into tables, so that readers can have a clearer view of the chapter content. This book also explains the important for an organisation to protect their vital records and the benefit of implementing records management programmes.